2020
DOI: 10.1016/j.jhazmat.2019.121179
|View full text |Cite
|
Sign up to set email alerts
|

Firefighters exposure to fire emissions: Impact on levels of biomarkers of exposure to polycyclic aromatic hydrocarbons and genotoxic/oxidative-effects

Abstract: Firefighters represent one of the riskiest occupations, yet due to the logistic reasons, the respective exposure assessment is one of the most challenging. Thus, this work assessed the impact of firefighting activities on levels of urinary monohydroxyl-polycyclic aromatic hydrocarbons (OHPAHs; 1-hydroxynaphthalene, 1-hydroxyacenaphthene, 2-hydroxyfluorene, 1-hydroxyphenanthrene, 1-hydroxypyrene, 3-hydroxybenzo(a)pyrene) and genotoxic/oxidative-effect biomarkers (basal DNA and oxidative DNA damage) of firefight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 93 publications
1
33
0
Order By: Relevance
“…PAHs metabolization occurs through complex biochemical reactions in the liver and in a lesser extent in the lungs, intestinal mucosa, skin, and kidneys in order to expedite their elimination from the human body [ 14 ]. PAHs are excreted through the urine, bile, milk, and feces in the form of hydroxylated compounds conjugated with macromolecules (glutathione, glucuronide, or sulphate) or as unmetabolized compounds [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Selected Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…PAHs metabolization occurs through complex biochemical reactions in the liver and in a lesser extent in the lungs, intestinal mucosa, skin, and kidneys in order to expedite their elimination from the human body [ 14 ]. PAHs are excreted through the urine, bile, milk, and feces in the form of hydroxylated compounds conjugated with macromolecules (glutathione, glucuronide, or sulphate) or as unmetabolized compounds [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Selected Chemicalsmentioning
confidence: 99%
“…Regarding firefighting forces, median values of total PAH metabolites varied between 1.59 µmol/mol creatinine in non-smoking and non-occupationally exposed firefighters to 6.96 µmol/mol creatinine in smoking and occupationally exposed individuals who were actively involved in firefighting activities; maximum levels reached 121 µmol/mol creatinine ( Table 1 ). Oliveira et al [ 27 ] reported concentrations of total PAH biomarkers that were up to 340% higher ( p ≤ 0.05) in subjects participating in firefighting comparatively with non-exposed firefighters. Moreover, those authors also found increased levels of oxidative stress in the blood cells of some exposed firefighters [ 27 ].…”
Section: Selected Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dioxins are released into the environment through natural sources such as volcanic activities or forest fires (Hay 1981). Such episodes are becoming more common with particular increases in the incidence of large-scale forest fires over the last decade (Salamanca et al 2016;Zhang et al 2016;Oliveira et al 2020). Dioxins are also discharged into the environment by various manufacturing processes involving synthesis of chlorinated aromatic and aliphatic compounds, such as pesticide and herbicides (Chen et al 2005) as well as paper production (Haq and Raj 2020).…”
Section: Sources Of Dioxins In the Environmentmentioning
confidence: 99%
“…Urinary 3hydroxybenzo(a)pyrene (3OHBaP) is a well-known biomarker of exposure to carcinogenic PAHs [24,25]. Increased levels of urinary OHPAHs in occupationally exposed groups have been associated with a higher prevalence of early markers of inflammation processes, cardiovascular disease, oxidative stress, and DNA damage [26][27][28].…”
Section: Introductionmentioning
confidence: 99%